The Rural Household Multi Indicator Survey (RHoMIS) tool is adopted as the standard monitoring and evaluation tool by TREE AID - CGIAR Research Program on Livestock (2019)
Humanitarian and environmental charity organisation, TREE AID, has adopted the Rural Household Multi Indicator Survey (RHoMIS) as their standard monitoring and evaluation tool to assess the effectiveness and impact of their projects. Surveys of beneficiaries are conducted at the beginning and end of each project, focusing on key indicators such as household income, fuel-wood usage, dietary diversity, use of trees and forests, natural resource management techniques and women’s decision-making powers.